Opening minds to translanguaging pedagogies. (August 2020) - Kirsch, Claudine
Abstract: Translanguaging pedagogies promise to capitalise on students' language backgrounds, improve their academic achievements and address social inequalities. While research studies in monolingual, bilingual and multilingual contexts testify to the benefits of translanguaging for learning, well-being and identity-building few studies focus on early childhood education and the use of more than two languages. Furthermore, little is known about the implementation of translanguaging pedagogies and the challenges faced by professionals. This article is based on a longitudinal research project which offered a professional development course to develop multilingual pedagogies in early childhood education in Luxembourg, where 63.7% of the 4-year-olds do not speak Luxembourgish as their home language. The article presents challenges which three practitioners faced when implementing a translanguaging pedagogy in their preschool classes as well as the ways in which they overcame them. They changed their negative stance to multilingual education, developed a social-constructivist leaning environment and monitored their language use. The findings shed light on the complexities of the implementation process and the support needed for professional learning.